In vitro and in vivo tropism and biodistribution of recombinant simian adenovirus type 25 - Irina V. Vavilova; Tatiana A. Ozharovskaia; Olga V. Zubkova; Olga Popova; Daria V. Voronina; Polina P. Goldovskaya; Denis I. Zrelkin; Alina Sh. Dzharullaeva; Inna V. Dolzhikova; Dmitry V. Shcheblyakov; Denis Yu. Logunov; Alexander L. Gintsburg (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Recombinant adenoviruses are widely used in the development of vaccines for a variety of infectious diseases. Despite numerous clinical studies, only a few types of human (types 5 and 26) and simian (isolate Y25) adenoviruses are currently used to produce vaccine formulations. Different types of adenoviruses vary in their cellular tropism, which plays a key role in their ability to elicit an immune response.